The Concise encyclopedia of ancient civilizations - Garber, Janet Serlin (New York : Watts, 1978)
Surveys ten great civilizations of the ancient world.
Includes index.
Keywords: Civilization, Ancient -- Dictionaries, Juvenile; Civilization, Ancient